Contextualization of Hadith About Rukyat and Hisab Perspective M. Syuhudi Ismail - Shinta Ratu Putri Unon Purwanto; Wirawan Seto Aji Pamungkas; Muhid (al-Afkar, Journal For Islamic Studies, 2024)
Understanding a hadith is not based on the meaning of the text alone, but also understanding the current context to apply religious teachings in the current situation. The contribution of contemporary such as Syuhudi Ismail is very important in the contextual understanding of hadith. This research aims to provide an understanding of the meaning of rukyat and hisab hadith, as well as identify M. Syuhudi Ismail's contextual understanding of rukyat and hisab hadith. The method used is descriptive with a library search, while the object of the research is the hadith narrated by Imam Bukari and Imam Muslim. The results this study provide an understanding that, Syuhudi Ismail provides an understanding that Muslims when they want to observe the new moon can use sophisticated tools such as telescopes and so on, because nowadays it is more modern where technology is very advanced. With the existence of these tools, they must be used as well as possible, so that Muslims today get more knowledge related to modern technology. Thus, the process observing the hilal is easier to do and of course the results are more accurate, compared to using the eyes like when the Prophet was still alive.